COMPARISON OF THE BRONCHODILATOR EFFICACY OF NEBULIZED PIRENZEPINE AND IPRATOPIUM BROMIDE IN PATIENTS WITH AIRWAY OBSTRUCTIVE LUNG-DISEASE - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 1993)
Ipratropium bromide (IB) is a non-selective muscarinic antagonist, whose bronchodilator efficacy has been shown in reversible and irreversible obstructive airway diseases. Pirenzepine is a M1 receptor antagonist and effective in vagally-induced bronchoconstriction. To investigate the bronchodilator efficacy of nebulized pirenzepine, we compared nebulized pirenzepine with nebulized IB and nebulized isotonic saline (placebo). Eighteen patients with reversible and 18 patients with irreversible obstructive airway disease were studied. Nebulized isotonic saline (placebo), 100 mcg nebulized pirenzepine and 125 mcg nebulized IB were given on three consecutive days. Spirometry was performed prior to nebulization and repeated at 5, 30, 60, 90 and 120 minutes following nebulized medication. A dose of 125 mcg IB resulted in a significant increase in FEV1 in patients with both reversible or irreversible bronchoconstriction (p <0.00001, p <0.03). IB at the same dose resulted in an increase in FVC in patients with irreversible bronchoconstriction (p <0.001) and an increase in FEF25-75 in patients with reversible bronchoconstriction (p <0.0003). Pirenzepine therapy resulted in no significant change in the same parameters. It is concluded that nebulized pirenzepine at a dose of 100 mcg does not have bronchodilator effect in patients with reversible or irreversible bronchoconstriction.
Keywords: PIRENZEPINE; IPRATROPIUM BROMIDE; REVERSIBLE AND IRREVERSIBLE BRONCHOCONSTRICTION; IPRATROPIUM BROMIDE; RECEPTOR SUBTYPES; PERIPHERAL LUNG; ASTHMA